Proteccion quimica del material de siembra de la yuca: Validacion de tecnologia en la Costa Atlantica de Colombia - Muñoz, F. (International Center for Tropical Agriculture, 1990)
The practice of treating cassava seed with chemicals was assessed on cassava growing farms in the departments of Cordoba, Sucre, Bolivar, and Atlantico (Colombia). On each farm the seed of cassava var. Venezolana was divided into 2 big lots: one of the lots was immersed in a solution of benomyl (3 g/l), maneb (3 g/l), and malathion (2 cc/l) for 5 min prior to planting. An additional factor was included the 2nd yr: seed origin (CIAT or the farmers). Significant differences were recorded the 1st yr among farmers for most of the variables under study. Treated plots had a higher final stand and a higher yield/ha (commercial plus noncommercial roots). No significant differences were recorded the 2nd yr regarding plant height, final stand, total wt. of aerial parts, and commercial and total root yields between treated and nontreated plots. The total no. of plants and the total wt. of aerial parts at harvest were significantly lower in the plots planted to farmers' seed compared with plots planted to CIAT seed; no significant differences, however, occurred in commercial root yield and total root yield. (CIAT)